Leadership in the VUCA world - a systematic literature review and its link to intercultural competencies. (26th July 2021) - Rath, Constanze Ruesga; Grosskopf, Sina; Barmeyer, Christoph
Today's world is characterised by change at a rapid pace. A concept that describes this demanding environment is the acronym VUCA - volatility, uncertainty, complexity and ambiguity. These four dynamics affect not only organisations but also leaders. Nevertheless, a comprehensive understanding of leadership under VUCA conditions remains vague. To fill this research gap, we conduct a systematic literature review to classify the existing leadership literature under VUCA conditions. Our research contributes to the field by synthesising the vast amount of literature, aiming for a more structured overview of research outcomes over the past 20 years (2000-2020). Since leadership is more and more a global activity in organisations, we furthermore analyse these findings from an intercultural perspective, linking the field of cross-cultural management, especially that of intercultural competence, to the leadership environment in the VUCA world.